Evaluation of a suicide prevention training curriculum for substance abuse treatment providers based on Treatment Improvement Protocol Number 50 (TIP 50) - Conner, Kenneth R. (2012)
Substance use disorders (SUD) confer risk for suicide yet there are no empirically supported suicide prevention training curricula tailored to SUD treatment providers. We assessed the efficacy of a 2-hour training that featured a suicide prevention training video produced by the Department of Veterans Affairs (VA). The video was based on Treatment Improvement Protocol Number 50, TIP 50, a practical manual to manage suicide risk produced by the Substance Abuse and Mental Health Services Administration (SAMHSA). The training was provided in small groups to 273 SUD treatment providers in 18 states. Results were evaluated using self-report assessments obtained at pre-test, post-test, and 2-month follow-up. Statistically significant changes (p<.001) within subjects were obtained on self-efficacy, knowledge, and frequency of suicide prevention practice behaviors. The positive results together with the brevity of the training and its ease of implementation indicate high potential for widespread adoption and the importance of further study.